Can Application of Artificial Intelligence in Enterprises Promote the Corporate Governance? - Cui, Xiuli; Xu, Bo; Razzaq, Amar (Frontiers in Environmental Science, 2022)
The impact of artificial intelligence (AI) on the economy and industry has gradually extended from the macroeconomic to the microeconomic level. Artificial intelligence technology has brought great innovation and impact to the company's operation and management and has a strong role in promoting the level of corporate governance. Based on an in-depth analysis of the theoretical mechanism of artificial intelligence affecting corporate governance, and based on the balanced panel data of Chinese A-share listed companies from 2011 to 2020, this paper empirically analyzes the mechanism and intermediary effect of artificial intelligence affecting corporate governance. The study found that AI applications can significantly improve corporate governance levels, and a higher level of artificial intelligence application can produce a higher level of corporate governance. From the perspective of the impact path, artificial intelligence technology can significantly improve the degree of information symmetry required for corporate governance, thereby providing favorable technical conditions and decision support for improving the level of corporate governance. Artificial intelligence technology has a positive and effective impact on corporate governance through the information symmetry effect.